Role of micronutrients in the management of coronavirus disease 2019. (November 2020) - AbdAllah, M.; Ez Elarab, H.; Raslan, E.; Saber, L.; Daoud, E.; Saber, M.
Abstract: Micronutrients play an important role in enhancing the immune system, therefore, proper nutritional support of micronutrients could have a positive impact on COVID-19 outcome.